Revitalisasi Perpustakaan Desa untuk Meningkatkan Minat Baca Anak di Desa Begendeng Kecamatan Jatikalen Nganjuk - Nurul Dwi Lestari; Dyah Ayu Wulandari (Fakultas Ushuluddin dan Komunikasi Islam, 2024)
Reading is an important thing to cultivate. Especially in the current information era, reading is a necessity for everyone. Education in Indonesia refers to the concept of learning throughout life (life long education). This concept means that throughout life humans continue to learn and one of the efforts that can be made in learning is reading. This service aims to develop and utilize libraries that already exist but are not yet running optimally as an effort to increase children's interest in reading. The library is a library located in Begendeng village. Begendeng Village is one of the villages located in Jatikalen District. This service activity uses the PAR method. In this activity, the servant carries out 5 stages of implementation, namely to Know, to Understand, to Plan, to Action, and to Reflection. The result of this service activity was the re-functioning of the library in Begendeng Village. Apart from that, children are also more enthusiastic and go to the library more often to read.